The Role of LPTQ in Enhancing the Achievements of Qari and Qari’ah : A Case Study in Kerinci - Pristian Hadi Putra; Masnur Alam (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to analyze the role of the Institute for the Development of Qur'anic Recitation (LPTQ) in enhancing the achievements of qari and qariah. LPTQ plays a crucial role as an institution not only responsible for organizing the Musabaqah Tilawatil Qur'an (MTQ) but also in supporting the continuous development of qari and qariah in various aspects, including recitation techniques, understanding of tajwid, and building confidence. This study uses a qualitative approach with a case study method, collecting data through in-depth interviews, observations, and document analysis. The role of LPTQ in enhancing the achievements of qari and qariah includes organizing the Musabaqah Tilawatil Qur’an, improving the quality of Qur'an reading, writing, and interpretation, holding selection/STQ events, and conducting Training Centers (TC). These findings indicate that LPTQ contributes significantly to improving the quality and achievements of qari and qariah in MTQ competitions. However, there are still obstacles that LPTQ Kerinci faces in increasing the achievements of qari and qariah, such as limited funds and resources, a shortage of qualified trainers, insufficient training facilities, limited training time, lack of government support, and a lack of tiered training programs. Recommendations from this study include increasing budget allocations, providing professional trainers, and developing sustainable programs to ensure the quality and continuity of LPTQ coaching.